Coronary Intimal Thickening Begins in Fetuses and Progresses in Pediatric Population and Adolescents to Atherosclerosis - Guerri Guttenberg, Roberto Andrés (2020)
The prevalence of coronary intimal thickening (IT) was assessed in fetuses and pediatric population. We studied the coronary arteries of 63 hearts obtained from fetuses, infants, children, and adolescents, deceased from noncardiac disease or trauma. Histomorphometric analysis, planimetry, and immunohistochemical studies were conducted. Intimal thickening consisted of proliferation of smooth muscle cells and scarce monocytes embedded in amorphous deposits within the internal elastic membrane (IEM). Intermingled lesions of intimal hyperplasia and parietal nonstenotic plaques were also observed. Intimal thickening was found in 10% of 20 fetuses, in 33.3% of 18 infants, 73.3% of 15 children, and 100% of 10 adolescents. A significant correlation (r = 0.671, P < 0.001) was found between the extent of IT and age. The IEM was duplicated or interrupted in 43% of patients, showing a positive correlation with the degree of IT (P = 0.01). Intimal thickening was predominantly found near bifurcation sites in the left anterior descending coronary artery (55.6%) and in zones free of bifurcation in the right coronary artery (75%). In conclusion, the prevalence and extension of IT lesions are higher at older ages within a young population. Intimal thickening may be regarded as the first event occurring in coronary preatherosclerosis, preceding lipid deposition.